The Security Dilemma: Managing Asylum Seeker and Refugee Policies in Response to Social Threats in Jakarta - Mahpudin; Sahliah Dita Arzikah (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2025)
The issue of asylum seekers and refugees is a global challenge that has a direct impact on recipient countries, including Indonesia. In DKI Jakarta, the presence of refugees has given rise to social polemics, such as public rejection of illegal refugee tents, which reflects the social impact and pressure on local infrastructure. This study aims to analyze the security dilemma in the management of asylum and refugee immigrant policies based on Presidential Regulation No. 125 of 2016, with a focus on the human security approach that includes positive (inclusive) and negative (exclusive) dimensions. Through qualitative methods with an instrumental case study approach, this study found that the state's position is not biased between the two sides of human security, namely: Inclusive human security, which is oriented towards refugee protection and Exclusive human security, which places citizens as the main priority. Existing policies have not been able to guarantee the protection of basic refugee rights while maintaining social stability. This study recommends a more holistic and collaborative policy approach and full commitment from the government, by looking at the socio-economic integration model of other countries such as Colombia. The implementation of structured, inclusive, and sustainable handling of asylum immigrants and refugees can not only improve protection for refugees, but also support social harmony and national stability, strengthening Indonesia's position in the international arena.